(untitled) (Research, Society and Development, 2021)
The absence of nomenclature, terminology and classification referring to the universe of startups may lead to inconsistencies in academic research. The purpose of this article is to systematize the nomenclature and terminology of the startups universe and establish a taxonomy of their own, as well as their classification considering both the academic and market point of view. Furthermore, to propose unique terms for academic use. The study used a Multivocal Review of the Literature on startups, verifying the nomenclatures, terminologies and classifications that guide it (phases, target audience, business model), both in academic literature and in gray literature. The result allowed the presentation of information so the various existing bases on the topic could be compared. The study used its own parameters and four data sources, which represents an opportunity for future studies on the subject, exploring other data sources and research methodologies. Moreover, the term "startup" is a widely used verb in the English language, which causes a lot of misunderstandings with what was called "startup" in this article. The study aims to contribute with a standard nomenclature model in order to achieve efficient analysis of the startups business language with the purpose of assisting researchers and entrepreneurs involved. The proposed definitions constitute a reference terminology with presentation of concepts of the startups’ terms, reconciling academic terminology with that used in the market in terms of target public, income model and stage.